2020
DOI: 10.3389/frobt.2020.565825
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Robot Behavior Impacts Perception of Intentionality and Gaze-Related Attentional Orienting

Abstract: Gaze behavior is an important social signal between humans as it communicates locations of interest. People typically orient their attention to where others look as this informs about others' intentions and future actions. Studies have shown that humans can engage in similar gaze behavior with robots but presumably more so when they adopt the intentional stance toward them (i.e., believing robot behaviors are intentional). In laboratory settings, the phenomenon of attending toward the direction of others' gaze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 78 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…Specifically, it is possible that the fact that the participants played engaging games (Simon Says and playing with Cozmo) in the control and one-time interaction (but not the repeated interaction) conditions immediately before performing the gambling task may have elevated their arousal and in turn impacted feedback processing. Additionally, worse learning outcomes specifically for the "Other" condition after repeated interaction would be in line with recent studies showing that repeated exposure to social robots negatively affects social cognitive processes (Abubshait & Wykowska, 2020). We suggest that reduced feedback monitoring for "Other" could be attributable to devaluation of the reward following repeated interactions with the robot.…”
Section: Figure 6 Learning Rates As a Function Of Condition And Recipientsupporting
confidence: 89%
“…Specifically, it is possible that the fact that the participants played engaging games (Simon Says and playing with Cozmo) in the control and one-time interaction (but not the repeated interaction) conditions immediately before performing the gambling task may have elevated their arousal and in turn impacted feedback processing. Additionally, worse learning outcomes specifically for the "Other" condition after repeated interaction would be in line with recent studies showing that repeated exposure to social robots negatively affects social cognitive processes (Abubshait & Wykowska, 2020). We suggest that reduced feedback monitoring for "Other" could be attributable to devaluation of the reward following repeated interactions with the robot.…”
Section: Figure 6 Learning Rates As a Function Of Condition And Recipientsupporting
confidence: 89%
“…Specifically, observers were able to exert top-down modulation of gaze-cueing when interacting with a robot endowed with characteristics that increased its social relevance (Abubshait & Wiese, 2017;Wiese et al, 2018;Wiese et al, 2012;Wykowska et al, 2014). These findings are also extended in more ecologically valid paradigms that measure gaze-cueing in real Human-Robot Interaction settings (Abubshait & Wykowska, 2020;Kompatsiari et al, 2017;2018). It has also been shown that robots can use social signals in more complex scenarios (i.e., head/gaze cue) to effectively convey messages during storytelling (Mutlu et al, 2006), to facilitate joint actions (Boucher et al, 2012), improve the perception of competence (Huang & Thomaz, 2011) and provide hints to solve tasks (Mutlu et al, 2006).…”
Section: Introductionmentioning
confidence: 61%
“…This study fits in with prior HRI literature that investigates under which conditions people adopt the intentional stance towards robots. Prior work has shown that factors such as a robots' physical appearance [1], behavior [16], exposure to reactive [42], or repetitive behavior [43] influence attribution of intentionality. Here, we illustrate that framing a task in a collaborative manner increases our tendency to adopt the intentional stance towards the robot.…”
Section: Discussionmentioning
confidence: 99%